ALGORITHM FOR DETERMINING PHOTORESIST CHARACTERISTICS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper presents data from a photoresist stady. Computational models have been developed to determine basic physical characteristics. A software algorithm for their derivation has been developed. Models for the calculation of basic characteristics such as integral sensitivity, efficiency, photoresist activation energy are presented. A number of statistical and mathematical analyses are presented.